SPATIAL FLOOD VULNERABILITY ASSESSMENT IN PENINSULAR MALAYSIA USING DATA ENVELOPMENT ANALYSIS (DEA) - Saharizan, Nurul Syuhada; Zahid, Zalina; Sheikh Husin, Siti Aida (Journal of Technology Management and Business, 2018)
Flood has caused an enormous negative impact on the environment and the population safety in Malaysia. Â Many areas are found to be vulnerable to flood due to heavy rainfall during monsoon seasons. However, not many studies were done to identify how vulnerable the prone areas are affected. This study focused on developing flood vulnerability measurement in Peninsular Malaysian states. Data Envelopment Analysis (DEA) was applied on a set of secondary data consisting of several input and output variables across 11 years from 2004 to 2014. The flood vulnerability index for each dimension was computed based on three aspects of flood vulnerability dimensions, i.e. the Population Vulnerability, the Social Vulnerability and the Biophysical Vulnerability. The result showed that Johor was the most vulnerable state among all the states in Peninsular Malaysia in terms of the Population Vulnerability. Meanwhile, Kelantan was the most vulnerable state in the Social Vulnerability and Kedah was the most vulnerable state in the Biophysical Vulnerability. The assessment of flood vulnerability can provide multi-information that may well contribute to a deeper understanding of flood disaster scenario in Malaysia.